Belonging in Australia not Turkey: The Sense of Belonging for Turkish Australians Living in Sydney - Ruhil Amal, Azmuddin; Mohammad Musab, Azmat Ali; Nor Yazi, Khamis (International Journal of Education and Research, 2013)
Sense of belonging and friendship are important aspects in ethnic identity. As such, the study explored the relationship between the sense of belonging and friendship of young Turkish Australian females in embracing their ethnic identity. Data was obtained from five young Turkish Australian females living in Sydney through two rounds of face to face interviews. The first round was semi-structured interviews while the second, after a month gap, was exploratory type of interviews to yield rich data. The analyses indicated deeper understanding of ethnic identity among the young participants through the sense of belonging and friendships developed. Inevitably other components of ethnic identity were found to be interwoven with the two, contributing significant roles in depicting the participants’ ethnic identity.